2010
DOI: 10.1375/twin.13.6.582
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic Twins With Neurofibromatosis Type 1 (NF1) Display Differences in Methylation ofNF1Gene Promoter Elements, 5' Untranslated region, Exon and Intron 1

Abstract: Neurofibromatosis type 1 (NF1) is a common autosomal dominant disorder caused by heterozygotic inactivation of the NF1 tumor suppressor gene at 17q11.2. The associated phenotypes are highly variable, and modifying genes have been proposed to explain at least in part the intriguing expressivity. Given that haploinsufficiency of the NF1 gene product neurofibromin is responsible for some of the clinical manifestations, variations in expression of the wildtype NF1 allele might modify the phenotype. We therefore in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In major depression, APP interacted with the abnormally expressed NF1. NF1 encodes a neurofibromin responsible for signal transduction, and has been associated with mental retardation and autism [52,94,95]. APP has been listed in the HGMD as being associated with schizophrenia [96].…”
Section: Discussionmentioning
confidence: 99%
“…In major depression, APP interacted with the abnormally expressed NF1. NF1 encodes a neurofibromin responsible for signal transduction, and has been associated with mental retardation and autism [52,94,95]. APP has been listed in the HGMD as being associated with schizophrenia [96].…”
Section: Discussionmentioning
confidence: 99%
“…A methylation study on the monozygotic twin pairs with NF1 that presented with several discordant features indicated that differences in the methylation patterns of the normal NF1 allele in twins may result in NF1 expression difference, thereby causing a modification of the NF1 phenotype (42). Comparing NF1 patients with a low number of cutaneous neurofibromas to those with a high number of cutaneous neurofibromas, using methylation-specific PCR and pyrosequencing, indicated that the promoter methylation of the mismatch repair MSH2 gene in the blood cells of patients was significantly different (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a pair of leukaemia-discordant twins has been described, in which the affected twin had a constitutive increase in methylation of BRCA1 (breast cancer 1, early onset) [64]. Similarly, in a pair of twins with the autosomal dominant neurofibromatosis type 1 (NF1), phenotypic severity was found to correlate with the level of methylation at the NF1 gene in lymphocytes [65]. Recently, a female twin pair was described in which both twins exhibited symptoms of Rett syndrome, an X-linked neurodevelopmental disorder, with only one twin meeting the full diagnostic criteria [66].…”
Section: Twins Disease Latency and Liabilitymentioning
confidence: 99%